Immediate Activation of Respiration in Petroselinum crispum L. in Response to the Phytophthora megasperma f. sp. Glycinea Elicitor. - Norman, E. G. (1994)
Treatment of parsley (Petroselinum crispum L.) cell cultures with the Phytophthora megasperma elicitor isolated from the fungus Phytophthora megasperma f. sp. Glycinea caused an immediate increase in the rate of respiratory CO2 evolution in the dark. The respiratory response was biphasic, showing a rapid enhancement in the first 20 min and then a slower increase until a steady rate was attained 60 min posttreatment. The enhanced rate of CO2 evolution corresponded to the activation of phosphofructokinase and glucose-6-phosphate dehydrogenase, key enzymes in the regulation of carbohydrate flow to glycolysis and the oxidative pentose phosphate (OPP) pathway, respectively. The increased rate of CO2 evolution and the activation of phosphofructokinase and glucose-6-phosphate dehydrogenase were maintained for the duration of the experiments, indicating long-term stimulation of respiration through both glycolysis and the OPP pathway. A 23% decrease in the C6:C1 ratio of 14CO2 evolution from labeled glucose 60 min after the addition of Phytophthora megasperma elicitor is consistent with an increased contribution of the OPP pathway to cellular respiration. Long-term activation of the OPP pathway following elicitation could serve to maintain the pools of substrates necessary during activation of the shikimic acid pathway, leading to the production of defensive compounds.